Outcomes following infant listing for cardiac transplantation: the impact of strategies introduced to counteract limited donor availability. Issue 11 (23rd July 2010) - Irving, C; Parry, G; Cassidy, J; Hasan, A; Griselli, M; Kirk, R
Abstract : Background: Survival following cardiac transplantation in infancy has improved substantially. There is a growing shortage of donors, the impact of which may be offset by increase in ABO-incompatible transplants, size-mismatching and mechanical support. The authors reviewed their results and outcomes following infant listing for cardiac transplantation over 22 years. Methods: Children <12 months at time of listing for cardiac transplant in 1987–2008 were identified using the departmental cardiopulmonary transplant database. Details were obtained from databases and hospital medical records and subdivided into two eras, 1987–1997 and 1998–2008. Results: In 1987–2008, 49 infants were listed, and 28 (57%) underwent cardiac transplantation (12 in 1987–1997 and 16 in 1998–2008). 15 patients (31%) died on the waiting list, 6 patients were delisted (5 of these because of recovery of cardiac function). There was a decrease in suitable donor offers from a mean of 36 per year in 1996–2000 to 11 per year in 2001–2006 (p=0.008). In 1998–2008, nine listed infants were on mechanical support; there were seven ABO-incompatible transplants, and all transplants were size-mismatched with donors on average 2.7 times heavier than recipients. Waiting times decreased from median 83 to 47 days. Six (21%) of the transplanted patients died, the majority in 1987–1997 and perioperatively. Conclusions: There has been a fall in suitable donors for infant cardiac transplants over time despite increased demand. However, the introduction of size-mismatching, ABO-incompatible transplants and mechanical support has enabled an increase in the number of transplants to be carried out despite this fall in donor numbers. Outcomes following transplantation have improved over time.